Hybrid power management for fuel cell/supercapacitor series hybrid electric vehicle - Veerendra, A. S.; Mohd Rusllim, Mohamed; Pui, Ki Leung; Shah, Akeel Abbas (Informa UK Limited, 2021)
The purpose of this study is to assess the potential improvement in fuel economy and performance of a fuel-cell series hybrid electric vehicle (FCHEV) in combination with a supercapacitor (SC) by using a hybrid power management (HPM) strategy. A combination of the extended Kalman filter (EKF) and traditional coulomb counting (CC) is used to conduct for estimating the SC state of charge. The combined Environmental Protection Agency (EPA) test cycles for a city and highway are considered in order to evaluate the fuel economy under realistic driving conditions. The HPM is able to deliver a maximum speed of 177 km/h, an enhanced fuel economy of 93.38 km/kg, 0–100 km/h acceleration in 9.0 seconds, a hydrogen consumption of 0.303 kg and a cruising range of 500 km for a FCHEV with a weight of 2180 kg. To place these figures in context, they are compared with the equivalent calculated figures for a 2017 Toyota Mirai fuel cell Electric Vehicle (FCEV).